Implementation of the power generation program by the Asian Infrastructure Investment Bank (AIIB) to improve the economy in Bangladesh - Zuha, Aulia Aisyah (Universitas Islam Malang, 2023)
This article examines the effectiveness of programs carried out by the Asian Infrastructure Investment Bank (AIIB) in encouraging economic investment and infrastructure connectivity in Asia. Specifically, the author will analyze AIIB assistance in Bangladesh in the electrical energy sector. AIIB is a multinational development bank initiated by China to encourage infrastructure in Asia. In terms of long-term funding for infrastructure sub-projects such as sub-projects in the areas of power production, ICT, cross-regional transportation, etc., AIIB has emerged as one of the most important development partners for Bangladesh. This paper aims to answer how effective the implementation of the electricity sector program by AIIB is in improving the economy in Bangladesh. To examine this topic, the author refers to Development theory and the concept of Global Governance. The results of the author's analysis show that most of the assistance provided by AIIB in Bangladesh focuses on the electrical energy sector, this is a response to the electricity crisis which is hampering the Bangladesh economy. The results of implementing the program are considered quite effective because it succeeded in distributing electricity evenly in villages and encouraging development renewable and low-carbon electrical energy infrastructure. However, this program can also be considered less effective because it has not been able to encourage Bangladesh to maximize its own natural resources to guarantee its electricity supply due to the low share of the renewable energy market in Bangladesh's electricity.